(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVES: CO2, Er:YAG and Nd:YAG lasers have been used in endodontic surgery. This in vitro study evaluated 1% Rhodamine B dye penetration using computer-assisted morphometry (ImageTool Software®) of 108 endodontically treated human permanent canines. MATERIAL AND METHODS: Teeth were divided into 9 groups according to the technique used: A: 90-degree apicoectomy with bur, root-end cavity preparation with ultrasound and filled with MTA; B: 90-degree apicoectomy with bur, root-end cavity prepared with ultrasound and filled with MTA, and treatment of apical surface with CO2 laser (1 W, CW/CW); C: 90-degree apicoectomy with bur, and treatment of apical surface with Nd:YAG laser (150 mJ, 10 Hz); D: 90-degree apicoectomy with bur, and treatment of apical surface with CO2 laser,(1 W, CW/CW); E: apicoectomy with Er:YAG laser (400 mJ, 10 Hz), root-end cavity prepared with ultrasound and filled with MTA; F: apicoectomy with Er:YAG laser (400 mJ, 10 Hz) and treatment of apical surface with Nd:YAG laser (150 mJ, 10Hz); G: apicoectomy with CO2 laser (5W, CW/SP), root-end cavity prepared with ultrasound and filled with MTA; H: irradiation of apical end with CO2 laser (1 W, CW/CW); I: irradiation of apical end with Nd:YAG laser (150 mJ, 10 Hz). RESULTS: Dye penetration was found in all specimens at different rates, the lowest penetration occurring in groups C (16.20%), B (17.24%) and F (17.84%). CONCLUSIONS: Groups B, C and F represent the best technical sequences to perform endodontic surgery.